Access to Justice for Women: A Comparative Study between Subarnachar and Begumganj Upazila of Noakhali District - Nazmun Sakib Ety; Badsha Mia (PT Mattawang Mediatama Solution, 2024)
Access to justice is the first step towards justice in the current legal system and is recognized as a fundamental human right in both the Constitution of Bangladesh and several international conventions. Despite this recognition, many Bangladeshi citizens, particularly women, face significant barriers to accessing justice due to gender and other factors. Access to justice is an important human right, but women in rural areas often face significant challenges in exercising this right. This study compares women's access to justice in two upazilas of Noakhali district: Subarnachar and Begumganj. By examining the sociocultural, economic and institutional elements that influence women's ability to seek and pursue legal remedies, this study highlights the differences between the two regions. Data obtained through interviews, questionnaires and focus group discussions with women, lawyers and community leaders. The study shows that while both upazilas face challenges such as patriarchal norms, lack of legal awareness and limited access to legal representation, the intensity and nature of these challenges differ significantly between Subarnachar and Begumganj. The findings highlight the need for targeted interventions that address the specific barriers faced by women in each upazila and promote equal access to justice. This study contributes to the broader discourse on gender and justice in Bangladesh and provides insights for policymakers, legal practitioners and civil society organizations working to reinforce the legal empowerment of women in rural areas.